National Seroprevalence of Coxiella burnetii in Chile, 2016–2017 - Teresa Tapia; María Fernanda Olivares; John Stenos; Rodrigo Iglesias; Nora Díaz; Natalia Vergara; Viviana Sotomayor; Doris Gallegos; Ricardo J Soares Magalhães; Johanna Acevedo; Pamela Araya; Stephen R Graves; et al. (Pathogens, 2021)
Coxiella burnetii is an intracellular bacterium and the cause of the zoonotic infection, Q fever. National surveillance data on C. burnetii seroprevalence is currently not available for any South American country, making efforts of public health to implement strategies to mitigate infections in different at-risk groups within the population extremely challenging. In the current study, we used two commercial anti-C. burnetii immunoassays to screen sera collected from a sample of the Chilean population as part of a 2016–2017 national health survey (n = 5166), nationwide and age-standardized. The seroprevalence for C. burnetii for persons ≥ 15 years was estimated to be 3.0% (95% CI 2.2–4.0), a level similar to national surveys from The Netherlands (2.4%) and USA (3.1%), but lower than Australia (5.6%). A linear increase of C. burnetii seropositivity was associated with an individual’s age, with the peak seroprevalence 5.6% (95% CI 3.6–8.6) observed in the ≥65 years’ group. C. burnetii seropositivity was significantly higher in the southern macro-zone 6.0% (95% CI 3.3–10.6) compared to metropolitan region 1.8% (95% CI 0.9–3.3), the former region being home to significant livestock industries, particularly dairy farming. These data will be useful to inform targeted strategies for the prevention of Q fever in at-risk populations in Chile.